1979
DOI: 10.1007/bf01477554
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate cyclase in human gastric mucosa: its activation by histamine in morphologically different biopsy specimens

Abstract: In morphologically different biopsy specimens from fundic, antral and duodenal mucosa of 134 persons, basal and histamine stimulated adenylate cyclase activity was studied: Basal and stimulated adenylate cyclase activities were log-normally distributed. Only in the fundic but not in the antral and duodenal mucosa adenylate cyclase was sensitive to histamine. The mean basal activity in the fundic gastric mucosa was 148, in response to 10(-5) mol/l histamine 292 pmol cAMP/mg protein/20 min. In human fundic biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This investigation has shown that basal, PGE2-and histamine-stimulated AC activi ties are log-normally distributed, so confirm ing earlier findings [3].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This investigation has shown that basal, PGE2-and histamine-stimulated AC activi ties are log-normally distributed, so confirm ing earlier findings [3].…”
Section: Discussionsupporting
confidence: 76%
“…Two were used for histological examination and the third one for estimation of AC activity. This sam ple was placed in an Eppendorf vial and stored at -2 0 °C until required [3). The patients were divided into 7 groups according to histological or clinical diag nosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated the relation between gastric inflammation and other markers including muscarinic receptors [59], adenylate cyclase [60], cell proliferation kinetics [61], anti-G cell antibody[57] and bacterial characteristics [62,63,64]. However, these markers have been discussed only in limited reports and have not been widely confirmed.…”
Section: Pepsinogen Gastrin and Gastric Acid Secretionmentioning
confidence: 99%
“…However, these tiny particles of sometimes less than 1 mg are also sufficient for biochemical investigations. In our studies on the regulation of human gastric mucosal adenylate cyclase [1][2][3], we have used biopsies and noticed that the inter pretation of the data on a pure histological basis, lacks sometimes information on the cellular composition of the biopsy, in partic ular on parietal cells. Thus, we looked for a method which would provide numerical data on parietal cells from single biopsies.…”
Section: Introductionmentioning
confidence: 99%